Python 3 : Pocket primer. - Parker, J. R. 1955- (Mercury Learning & Information, 2018)
Providing programmers with a sufficient knowledge of Python 3 to be able to work on their own projects, this book covers all of the basic concepts and features a chapter on PyGame, which allows a programmer to handle graphics, mouse and keyboard interaction, and play sounds and videos. -- Edited summary from book.
Keywords: Python (Computer program language); Computer programming.; Video games -- Programming.; elektronické knihy; electronic books